2008
DOI: 10.1111/j.1365-2486.2008.01672.x
|View full text |Cite
|
Sign up to set email alerts
|

Global decomposition experiment shows soil animal impacts on decomposition are climate‐dependent

Abstract: Climate and litter quality are primary drivers of terrestrial decomposition and, based on evidence from multisite experiments at regional and global scales, are universally factored into global decomposition models. In contrast, soil animals are considered key regulators of decomposition at local scales but their role at larger scales is unresolved. Soil animals are consequently excluded from global models of organic mineralization processes. Incomplete assessment of the roles of soil animals stems from the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
354
8
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(401 citation statements)
references
References 37 publications
(56 reference statements)
21
354
8
5
Order By: Relevance
“…It is obvious from the above and further studies (Schmidt 2006;Yin 1999;Wall et al 2008;Freschet et al 2012b) that the different abiotic and biotic drivers of wood decomposition dynamics interact strongly. Also, different species are found in different environments and this makes it difficult to disentangle the species wood trait effects from the effects of the other drivers.…”
Section: The Challenge: Disentangling the Interacting Effects Of Woodmentioning
confidence: 94%
“…It is obvious from the above and further studies (Schmidt 2006;Yin 1999;Wall et al 2008;Freschet et al 2012b) that the different abiotic and biotic drivers of wood decomposition dynamics interact strongly. Also, different species are found in different environments and this makes it difficult to disentangle the species wood trait effects from the effects of the other drivers.…”
Section: The Challenge: Disentangling the Interacting Effects Of Woodmentioning
confidence: 94%
“…This result suggests that fauna plays a key role in litter diversity effects on decomposition, at least in this neotropical study system. Although decomposition is largely driven by microorganisms, fauna can contribute significantly [17], particularly in tropical rainforests [3], and litter-feeding fauna has to deal with similar stoichiometric constraints as microbial decomposers do [18]. Because fauna is more mobile than microorganisms, they can more easily switch between individual leaves of different plant species which might explain a stronger impact of stoichiometric dissimilarity of litter mixtures on mixture decomposition when fauna is present [16].…”
Section: Introductionmentioning
confidence: 99%
“…chemical and physical characteristics of litter) and soil biota [1][2][3]. Among these, litter chemical quality explains most of the variation in leaf litter decomposition rates at the global scale [4], with consistent litter chemical quality driven differences among litter types across large environmental gradients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Another study also highlighted the main role of climate on breakdown in cold areas of the Northern Hemisphere [10], whereas several terrestrial studies at the global scale found that effects of litter quality on breakdown were greater than effects of climate [11 -13]. Detritivores can also be important contributors to breakdown rates in terrestrial ecosystems [9], particularly in temperate and wet tropical climates where biological activity is not constrained by temperature or moisture [14].…”
Section: Introductionmentioning
confidence: 99%
“…We expected that the relative importance of litter quality and PD, detritivore presence, climate and other environmental factors would vary globally, based on the existing evidence from terrestrial ecosystems [9,11,13,14]. We hypothesized that (i) microbial breakdown would increase with temperature (through its effect on metabolic rate [36,37]), and hence decrease with latitude; (ii) detritivore-mediated breakdown would be greater at higher latitudes, where litter-consuming detritivores are more abundant and diverse [38]; (iii) litter of high quality would break down rapidly [24,26]; (iv) phylogenetically diverse plant litter would break down faster because of the potential presence of a wider range of species trait values, which increases the chance for niche partitioning [39]; (v) more basic water (higher pH) would enhance breakdown, as is typically the case [40]; (vi) breakdown would be faster in narrower streams where litter retentiveness is generally higher [41]; and (vii) climate would modulate the effects of other environmental factors and litter on breakdown rates; for example, higher temperatures could enhance any effects of litter quality or water chemistry [42].…”
Section: Introductionmentioning
confidence: 99%